2019
DOI: 10.1007/s40520-019-01384-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of cognitive resources on everyday functioning among oldest-old physically frail

Abstract: Background: Everyday functioning becomes a challenge with aging, particularly among frail oldest-old adults. Several factors have been identified as influencing everyday activities realization, including physical and cognitive functioning. However, the influence of cognitive resources as a compensatory factor in the context of physical frailty deserves further consideration. Aims: This study aims to investigate in older adults physically frail the possible compensatory role of cognitive resources to perform ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…This in turn might mean that cognitive abilities, including speed as a crucial cognitive ability marker, function as a compensatory resource that gains in importance to maintain functional health when pain sets in or worsens. A similar compensatory role of cognitive resources was reported with regard to health conditions other than pain, for example, for older adults with sensory impairments (Heyl & Wahl, 2012) or in oldest-old individuals who are physically frail (Dupuy, N'Kaoua, Dehail, & Sauzéon, 2019).…”
Section: Do Accommodative Coping and Information-processing Speed Mod...supporting
confidence: 55%
“…This in turn might mean that cognitive abilities, including speed as a crucial cognitive ability marker, function as a compensatory resource that gains in importance to maintain functional health when pain sets in or worsens. A similar compensatory role of cognitive resources was reported with regard to health conditions other than pain, for example, for older adults with sensory impairments (Heyl & Wahl, 2012) or in oldest-old individuals who are physically frail (Dupuy, N'Kaoua, Dehail, & Sauzéon, 2019).…”
Section: Do Accommodative Coping and Information-processing Speed Mod...supporting
confidence: 55%
“…The original study reported moderately significant associations (R 2 0.14-0.29) between the TIADL and the Useful Field of View (UFOV ® ), the Rey Auditory-Verbal Learning Test, and the Word Series test [15]. The TIADL has been used frequently [23][24][25].…”
Section: Tiadl-original Versionmentioning
confidence: 99%
“…What's more, we do not know to what extent laboratorybased cognitive tasks can predict real-life outcomes in older adults: older adults often function competently in complex everyday situations despite age-related deficits on laboratorybased cognitive tasks (86). Several factors have been identified as influencing everyday activities realization, including physical and cognitive functioning (87). However, there is little evidence that interventions improve performance on distantly related tasks or that training improves everyday functioning in later life (88).…”
Section: Long-term E Ects Of Cochlear Implantation and Comparisonmentioning
confidence: 99%